Primary malignant melanoma of uterine cervix with probable origin from benign cervical melanosis - Singh, Nilanchali (BMJ Publishing Group, 2013)
We report a case of primary malignant melanoma of cervix which is a rare malignancy with only around 60 cases being reported. This patient presented with bleeding per vaginum. A large exophytic growth from cervix with black discolouration was seen. International Federation of Gynaecology and Obsterics (FIGO) staging was stage IIa. Histoimmunocytology confirmed the diagnosis of malignant melanoma of cervix. S-100 and HMB-45 are reliable markers for cervical melanomas. We attempted Wertheim's hysterectomy; but, due to extensive disease, paravescical and pararectal fossae could not be dissected and we had to perform type I hysterectomy. The patient was started on adjuvant chemotherapy with dacarbazine. Despite counselling, she refused a complete course of chemotherapy and died after 6 months. Radical surgery, chemotherapy and immunotherapy are the therapeutic modalities used. In bulky disease, neoadjuvant chemotherapy should be considered to reduce the tumour bulk and facilitate required surgery. Prognosis is poor and unpredictable.